The impact of regulatory fit on performance in an inattentional blindness paradigm - Memmert, Daniel; Unkelbach, Christian; Ganns, Steffen (The Journal of general psychology, 2010)
When people's self-regulatory focus (e.g., focus on gains vs. focus on avoiding losses) matches environmental demands (e.g., search gains vs. avoid losses), Regulatory Focus Theory predicts performance improvements because of “regulatory fit” (Higgins, 1997). In this article, the authors investigate attentional differences due to regulatory fit as a possible cause for changes in performance, using an inattentional blindness paradigm. Participants counted passes in a basketball game, during which an unexpected object appears (in the present study, a gorilla). We measured participants’ chronic self-regulatory focus with a standardized questionnaire and experimentally manipulated their situational focus. If experimental focus fitted chronic focus, more participants detected the unexpected object compared to the nonfit conditions, suggesting that fit led to a broader scope of attention. The data are discussed in relation to other cognitive consequences of regulatory fit, and how these might explain performance differences in a wide range of tasks that do not directly follow from Regulatory Focus Theory.